2005
DOI: 10.1111/j.1467-2494.2005.00235.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione as a depigmenting agent: an overview

Abstract: Glutathione is an ubiquitous compound found in our bodies. Aside from its many ascribed biologic functions, it has also been implicated in skin lightening. We review in vitro and in vivo studies that show evidence of its involvement in the melanogenic pathway and shed light on the its anti-melanogenic effect. Proposed mechanisms of action include: (a) direct inactivation of the enzyme tyrosinase by binding with the copper-containing active site of the enzyme; (b) mediating the switch mechanism from eumelanin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 49 publications
0
71
0
Order By: Relevance
“…However, treatments with CC-EO and cinnamaldehyde resulted in a dose-dependent attenuation of the α-MSH-stimulated formation of cellular oxidants (Figure 4A,B). The GSH level is important for maintaining cellular redox status and plays an important role in the inhibition of melanogenesis [35]. Our data indicated that compared with unstimulated control cells, stimulation by α-MSH caused a 47% decrease in GSH levels ( p < 0.05); however, a dose-dependent recovery of α-MSH-reduced GSH levels was observed in the presence of CC-EO and cinnamaldehyde (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 71%
“…However, treatments with CC-EO and cinnamaldehyde resulted in a dose-dependent attenuation of the α-MSH-stimulated formation of cellular oxidants (Figure 4A,B). The GSH level is important for maintaining cellular redox status and plays an important role in the inhibition of melanogenesis [35]. Our data indicated that compared with unstimulated control cells, stimulation by α-MSH caused a 47% decrease in GSH levels ( p < 0.05); however, a dose-dependent recovery of α-MSH-reduced GSH levels was observed in the presence of CC-EO and cinnamaldehyde (Figure 4C,D).…”
Section: Resultsmentioning
confidence: 71%
“…Its antimelanogenic properties result from a variety of mechanisms including stimulation of pheomelanin synthesis rather than darker eumelanin, its antioxidant effects,14 and interference with intracellular trafficking of melanogenic enzymes 15. Glutathione also possesses certain antiaging properties 16…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 20  μ g/mL VZ-EO decreased the α -MSH-stimulated MDA levels to a level that was almost the same as that observed in unstimulated cells. The level of GSH is important for maintaining the cellular redox status and plays an important role in the inhibition of melanogenesis [25]. Our data indicated that the GSH level in B16 cells was reduced by α -MSH treatment to only 43.7 nmol/mg protein.…”
Section: Resultsmentioning
confidence: 79%